Agreement between numerical integration techniques during countermovement jumps with accentuated eccentric loading in youth athletes - Bright, T. E.; Lake, J.; Harry, J. R.; Hite, M.; Simms, A.; Theis, N.; Mundy, P.; Hughes, J. D. (Journal of Sports Sciences, 2025)
This study evaluated agreement between a) force platform numerical integration techniques for calculating performance variables and b) three-dimensional (3D) motion capture and vertical ground reaction force (vGRF) methods for identifying the dumbbell release during countermovement jumps with accentuated eccentric loading (CMJAEL). Twenty adolescent participants (10 males, 10 females) performed CMJAEL with handheld dumbbells at 20%, 25% and 30% of body mass. Variables were compared across five integration methods using repeated measures Bland-Altman and two-way repeated measures ANOVA analyses (a = 0.05), with combined forward and backward integration serving as the criterion. Backward integration and after adjusting at the dumbbells release agreed with the criterion, while forward integration and adjusting at the bottom position did not. The dumbbell release point identified using 3D motion capture (criterion) was also compared to estimates derived from force platform data (vGRF method). The vGRF method identified the dumbbell release point in delay of 3D motion capture, with limits of agreement (LOA) between -0.17 and 0.03 s across conditions. These methods should not be used interchangeably; rather, we recommend that the vGRF method be used in situations whereby only force platforms are available, and that it is combined with forward and backward integration techniques.